The Incidence and Management of Postdural Puncture Headache in Patients Undergoing Percutaneous Lead Placement for Spinal Cord Stimulation. Issue 7 (12th May 2016) - Simopoulos, Thomas T.; Sharma, Sanjiv; Aner, Musa; Gill, Jatinder S.
Abstract : Background: Spinal cord stimulation (SCS) is rapidly expanding therapy for the treatment of refractory neuropathic pain. Although technical issues such as battery life and lead migration have been well studied and improved, little is known about the incidence and management of inadvertent dural puncture and consequent headache. Objectives: The goals of this article were to determine the incidence of postdural puncture headache (PDPH) per lead insertion at the various regions of the spine and to detail the use of conservative management and epidural blood patch (EBP). Long‐term outcomes are reviewed to validate treatment modalities employed. Methods: Retrospective analysis of electronic medical records identified by patient implant registry and current procedural terminology data for nearly a 13‐year time interval. Operative and postoperative notes were reviewed for details on dural puncture, access technique and spinal level, the development of a PDPH, and the treatment employed with particularly emphasis on the use of (EBP). Results: A total of 745 leads inserted resulted in 6 PDPH that were refractory to conservative measures but responded to EBP without long‐term complications. The overall incidence of PDPH per lead insertion was 0.81%. Leads placed anterograde in the thoracolumbar (T11‐L3) and Cervicothoracic (C7‐T5) regions resulted in an incidence of PDPH per lead of 0.63% and 1.1%, respectively, while 5.9% occurred with lumbar retrograde approach, and none with caudal. Conclusions: Dural puncture during SCS device placement and can result in a PDPH that is severe and refractory to conservative modes of therapy. Even in the presence of hardware, EBP performed with meticulous aseptic technique was found to be safe and efficacious.